Simultaneous detection of phosphatidylcholines and glycerolipids using matrix‐enhanced surface‐assisted laser desorption/ionization‐mass spectrometry with sputter‐deposited platinum film. (23rd September 2015) - Ozawa, Tomoyuki; Osaka, Issey; Ihozaki, Taisuke; Hamada, Satoshi; Kuroda, Yusuke; Murakami, Tatsuya; Miyazato, Akio; Kawasaki, Hideya; Arakawa, Ryuichi
Abstract : Matrix‐assisted laser desorption/ionisation (MALDI) imaging mass spectrometry (IMS) allows for the simultaneous detection and imaging of several molecules in brain tissue. However, the detection of glycerolipids such as diacylglycerol (DAG) and triacylglycerol (TAG) in brain tissues is hindered in MALDI‐IMS because of the ion suppression effect from excessive ion yields of phosphatidylcholine (PC). In this study, we describe an approach that employs a homogeneously deposited metal nanoparticle layer (or film) for the detection of glycerolipids in rat brain tissue sections using IMS. Surface‐assisted laser desorption/ionisation IMS with sputter‐deposited Pt film (Pt‐SALDI‐IMS) for lipid analysis was performed as a solvent‐free and organic matrix‐free method. Pt‐SALDI produced a homogenous layer of nanoparticles over the surface of the rat brain tissue section. Highly selective detection of lipids was possible by MALDI‐IMS and Pt‐SALDI‐IMS; MALDI‐IMS detected the dominant ion peak of PC in the tissue section, and there were no ion peaks representing glycerolipids such as DAG and TAG. In contrast, Pt‐SALDI‐IMS allowed the detection of these glycerolipids, but not PC. Therefore, using a hybrid method combining MALDI and Pt‐SALDI (i.e., matrix‐enhanced [ME]‐Pt‐SALDI‐IMS), we achieved the simultaneous detection of PC, PE and DAG in rat brain tissue sections, and the sensitivity for the detection of these molecules was better than that of MALDI‐IMS or Pt‐SALDI alone. The present simple ME‐Pt‐SALDI approach for the simultaneous detection of PC and DAG using two matrices (sputter‐deposited Pt film and DHB matrix) would be useful in imaging analyses of biological tissue sections. Copyright © 2015 John Wiley & Sons, Ltd.